Matter Flow Through an Animal Model Feed With Grasshopper Sphenarium purpurascens: Evidence of a Sustainable and Nutritious Protein Production System - Meza-Cureño, Lluvia Topacio; Mendieta Sánchez, Adela Monserrat; Castillo, Ana Maria; Cabello Hernandez, Christian; Carmona, Agustin; Alavez, Valeria; Martínez, Yuriana; Garcia-Cuenca, Edilberto; Cano-Santana, Zenón; Cerritos, René (Frontiers in Sustainable Food Systems, 2022)
The demand for food and the environmental damage linked to its production will increase significantly; thus, the need for protein sources that are nutritious, digestible, and sustainable in environmental terms is rising. Many bromatological studies show that insects possess high protein amounts, becoming an alternative to conventional livestock. However, in vivo studies on digestibility are scarce (either on humans or laboratory animals), particularly when analyzing assimilation efficiency. In this work, we measured weight gain, food intake, feces and urine quantification, protein assimilation efficiency, and food conversion ratio in Wistar rats fed with five different diets for 5 weeks. Three diets were based on different concentrations of orthopteran protein (Sphenarium purpurascens) and were compared against a control diet and a highly caloric treatment, which was heavy in sugar and refined flours. The diet based on 23% of S. purpurascens protein resulted in 2.0 and 20.8% more biomass accumulation than the control and the highly caloric diet, respectively. The diets with 18% and 23% insect protein exhibited an average feed conversion of 6.3, while the control group resulted in 8.5 and the caloric diet in 42.7. These results show that S. purpurascens protein yields higher or equal conversion values than a conventional diet, indicating that grasshoppers can be a sustainable and nutritious food for humans and an alternative to livestock. On the other hand, even if feeding insects to farm animals for human consumption is considered an option, it seems highly inefficient, mainly because this practice increases one trophic level in the energy flow. Therefore, incorporating insect protein into human diets represents a sustainable alternative to face future feeding and environmental challenges. Proposals like the one we present here have yet to be evaluated; however, our findings in laboratory animals project a promising future for human populations, where low environmental cost proteins could be obtained sustainably.